Caregiver Burden Domains and Their Relationship with Anxiety and Depression in the First Six Months of Cancer Diagnosis - Francisco García-Torres (International Journal of Environmental Research and Public Health, 2020)
Cancer caregiving is associated with burden and a poor psychological state. However, there is no previous information about the predictive utility of specific burden domains on anxiety and depression in the first six months after a partner’s cancer diagnosis. In a longitudinal study, 67 caregivers completed the Zarit Burden Interview (ZBI) and Hospital Anxiety and Depression Scale (HADS) at T1 (45–60 days after diagnosis) and T2 (180–200 days after diagnosis). Most of the caregivers were female (65.7%, mean age = 51.63, SD = 13.25), while patients were mostly male (56.7%). The TRIPOD checklist was applied. ZBI scores were moderate and HADS anxiety reached significant values. There were no differences in ZBI and HADS between T1 and T2. The relationship between burden, anxiety, and depression were more consistent at T2, while emotional burden at T1 were related and predicted anxiety and depression at T2. Some burden domains were related and predicted anxiety in caregivers in the first six months after partner cancer diagnosis. This information could be useful to prevent the onset of these symptoms in the first six months after diagnosis.